Efforts To Improve The Ability To Understand Values Educative In Mirrors Through The Circ Model (Cooperative Integrated Reading And Composition) Students Class XI Sma N 1 Sugunung - Siti Hazizah Angkat (UMSU, 2020)
This Classroom Action Research (CAR) aims to describe (1) the activity student learning during the application of the CIRC learning model, (2) response students towards the application of the CIRC learning model, (3) increasing learning outcomes students to achieve the level of completeness of student learning outcomes in activities understand the educational values in short stories by applying the learning model CIRC, (4) steps taken in implementing the CIRC model. Subject research are the teachers and students of class XI and SMA N 1 SIGUNUNG that numbering 40 people. The object of this research is student learning activities, improvement results , responses and learning steps in applying the model CIRC learning . The data collection method used in this study are the test method, observation method, interview and questionnaire method. Data analyzed using quantitative descriptive and qualitative descriptive techniques. The results of this study were (1) the students were seen to be active in carrying out activities learning , (2) students give very positive responses to application CIRC learning model in short story learning (3) achieving completeness results learn to understand the educational values in students' short stories thanks to the application of the model CIRC learning , namely the pre-action classical average score of 68, cycle I obtained a classical average score of 77, while in the second cycle the classical average score students become 90 and (4) there are several steps for implementing the learning model CIRC to increase activities and achieve mastery learning outcomes understand the educational values in short stories. These steps are emphasized in literature learning, especially short stories that were previously invited to read without intensive understanding it is better to apply the modelCIRC which emphasizes students to learn in groups and integrate reading and writing as a reference for understanding literature. Based on the results research , other researchers are advised to apply the CIRC learning model, as an innovative learning model, in other language subjects in general and in Indonesian lessons, in particular. Key words: CIRC learning, understanding ability, educational values